Prognosis in Thai colorectal-cancer patients with GSTM1 and GSTT1 copy number variation - Pongtheerat, Tanett; Chaksangchaichot, Panee; Saelee, Pensri (European Journal of Oncology and Environmental Health, 2014)
Background: Glutathione S-transferase (GST) enzymes including GSTM1 and GSTT1 are involved in the detoxification of carcinogenic compounds. Null genotypes of GSTM1 and GSTT1 may result in reduced enzyme activity and be associated with susceptibility to various cancers. The detection of DNA copy number variation (CNV) by real-time PCR is reportedly very effective for detecting GSTM1 and GSTT1. This study investigated the association between GSTM1 and GSTT1 copy number variations and clinico-pathological parameters and gene copy number variation, and their potential relationship with the survival status of colorectal-cancer patients. Methods: Fifty-three Thai colorectal-cancer patients were investigated for GSTM1 and GSTT1 copy number variation by real-time PCR. Correlations between gene copy number variation and clinico-pathological characteristics were analyzed. Results: The results showed an association between GSTM1 copy number variation with stage and lymph-node metastasis. Increases in GSTM1 copy number were related to a negative prognosis and reduced survival status of patients. No association was found between GSTT1 copy number variation with patients’ clinico-pathological parameters and survival. Conclusions: The results demonstrated that GSTM1 copy number variation may be used in guiding the prognosis for Thai colorectal-cancer patients.